PROVISION OF HUMAN WASTE DISPOSAL FACILITIES IN NKANU WEST LOCAL GOVERNMENT AREA OF ENUGU STATE - ANI, NGOZIRITA, ANI, NGOZIRITA; UGWUOKE, ANTHONY CHUKWURA, UGWUOKE, ANTHONY CHUKWURA (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
The research was aimed at determining the levels of provision of human waste disposal and hand washing facilities in Nkanu West Local Government Area of Enugu state. Two research questions were posed to guide the study while only one null-hypothesis was formulated and was tested at .05 level of significance. A cross-sectional survey research design was used for the study. The sample for the study comprised 381 household heads. Questionnaire was utilized to generate data from the respondents. Frequencies and percentages were used to analyze the responses and also to answer the research questions posed to guide the study. Chi-square statistic was used to test the association between gender and types of toilet facilities provided. Results from the study indicated a high level of provision of toilet facilities (74.5%) in the area. However, there was very low provision of wash hand basin (24.4%) in the area. The Chi-square test showed that there was no significant association between gender and types of toilet facilities provided in Nkanu west LGA (cal.c = 2.78 < tab.c2 = 3.84, df =1,p < .05). Based on the finding it was recommended that relevant authorities should enforce sanitation laws in the area to make the LGA open defection free. Furthermore, health education should be vigorously carried out on need for households to provide toilets and wash hand basins.